Exposure of yellow-legged gulls to Toxoplasma gondii along the Western Mediterranean coasts: Tales from a sentinel. (April 2019) - Gamble, Amandine; Ramos, Raül; Parra-Torres, Yaiza; Mercier, Aurélien; Galal, Lokman; Pearce-Duvet, Jessica; Villena, Isabelle; Montalvo, Tomás; González-Solís, Jacob; Hammouda, Abdessalem; Oro, Daniel; Selmi, Slaheddine; et al.
Abstract: Efficiently tracking and anticipating the dynamics of infectious agents in wild populations requires the gathering of large numbers of samples, if possible at several locations and points in time, which can be a challenge for some species. Testing for the presence of specific maternal antibodies in egg yolks sampled on the colonies could represent an efficient way to quantify the exposure of breeding females to infectious agents, particularly when using an abundant and widespread species, such as the yellow-legged gull ( Larus michahellis ). We used such an approach to explore spatio-temporal patterns of exposure to Toxoplasma gondii, a pathogenic protozoan responsible of toxoplasmosis in humans and other warm-blooded vertebrates. First, we tested the validity of this approach by exploring the repeatability of the detection of specific antibodies at the egg level using two different immunoassays and at the clutch level using an occupancy model. Then, samples gathered in 15 colonies from France, Spain and Tunisia were analysed using an immunoassay detecting antibodies specifically directed against T. gondii . Prevalence of specific antibodies in eggs was overall high while varying significantly among colonies. These results revealed that T. gondii circulated at a large spatial scale in the western Mediterranean yellow-legged gull population, highlighting its potential role in the maintenance community of this parasite. Additionally, this study illustrates how species commensal to human populations like large gulls can be used as wildlife sentinels for the tracking of infectious agents at the human-wildlife interface, notably by sampling eggs. Graphical abstract: Image 1 Highlights: Yellow-legged gulls are widely exposed to Toxoplasma gondii. Gulls could be involved in the maintenance and circulation of T. gondii. Eggs represent an efficient alternative to blood samples for serosurvey. Large gulls may be used as epidemiological sentinels at the human-wildlife interface.